Elevated Serum and Cerebrospinal Fluid CD138 in Patients With Anti-N-Methyl-d-Aspartate Receptor Encephalitis - Zhu, Jiajia; Li, Yongqi; Zheng, Dong; Wang, Zhanhang; Pan, Suyue; Yin, Jia; Wang, Honghao (Frontiers in Molecular Neuroscience, 2019)
Background: Syndecan-1 is an important component of endothelial cell glycocalyx, and has been reported to be a negative regulator of various inflammatory processes. The clinical implication of circulating and CSF syndecan-1 (sCD138) in patients with anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis remains unclear. Objective: We aimed to investigate the association of serum and CSF syndecan-1 levels in anti-NMDAR encephalitis patients. Methods: A total of 27 patients with anti-NMDAR encephalitis, 11 viral meningoencephalitis and 22 controls were enrolled in this study. At the time of admission and 3-6-month follow-up, all patients, were measured sCD138, TNF-α, MMP-2 and MMP-9 in serum and CSF by enzyme-linked immunosorbent assay. Results: Serum and CSF levels of sCD138 were significantly increased in patients with anti-NMDAR encephalitis. Furthermore, at 3-6 months follow-up, CSF levels of sCD138 were significantly decreased in anti-NMDAR encephalitis patients. Changes of sCD138 levels also significantly correlated to ameliorate of mRS scores in patients with anti-NMDAR encephalitis. Conclusions: In anti-NMDAR encephalitis patients, high circulating and CSF sCD138 is associated with inflammation and poor clinical prognosis. In this study, we present data supporting the sCD138 as a new biomarker for inflammation of anti-NMDAR encephalitis.